Outcome of pneumatic lithotripsy versus holmium laser in distal ureteric stones - Rasheed, Rafat; Haroon Sabir khan; Muhammad Tanveer Sajid; Syed Yazdan Haider; Badar Murtaza; Nubair Sarwar (International Journal of Pathology, 2025)
Background: The prevalence of distal ureteric stones (DUS) is a serious urological disease having a high morbidity. Pneumatic lithotripsy (PL) and holmium laser lithotripsy (HL) are popular modalities of treatment with HL usually reported to have superior results albeit at increased cost. This study aims at comparing the safety and efficacy of HL and PL in the management of DUS. Methods: This observational comparative study was conducted at Armed Forces Institute of Urology, Rawalpindi, from Feb to September 2025, including 160 patients of DUS (<2 cm) schedule for either procedure was enrolled and divided in HL or PL, each consists of 80 individuals. One-month stone-free status were analyzed through SPSS-27, with p≤0.05 considered significant. Results: Groups were compared at baseline regarding age (55.9 ± 11.7 vs. 57.7 ± 10.5 years, p=0.72), gender (p=0.07), BMI (p=0.64), comorbidities, and stone size (p=0.18). Operative time was similar (47.4 ± 2.6 vs. 43.1 ± 4.2 min, p=0.58). HL resulted in significantly lower postoperative pain scores (VAS 3.3 ± 1.2 vs. 6.6 ± 1.5, p<0.001), shorter hospital stays (<24h: 85% vs. 56.3%, p<0.001), and higher stone-free rates at one month (97.3% vs. 79.4%, p<0.001). Intraoperative hemorrhage (p=0.12), ureteral injury (p=0.56), fever (p=0.24), and infection (p=0.14) were infrequent and not significantly different. Conclusion: HL provides superior efficacy, reduced pain, and shorter hospitalization compared to PL, while maintaining comparable safety. However, PL remains a feasible option in resource-limited settings.